ANALISIS HUBUNGAN KAUSALITAS PENDAPATAN NASIONAL DENGAN DEPOSITO SYARIAH DAN DEPOSITO NON SYARIAH DI INDONESIA (PERIODE 2004-2013) - B01111007, DIKA B01111007 ANUGRAH JANUARI (Jurnal Pembangunan dan Pemerataan, 2016)
AbstractThis research aimed to analyze the causal relationship between the national income and the Sharia-compliant savings and non-Sharia-compliant savings in Indonesia from 2004-2013 where the Sharia-compliant savings was the dependent variable (Y1) and non-Sharia-compliant savings (Y2), while the national income (GDP) as the independent variable (X). The testing stages used the OLS (Ordinary Least Square) method, stationarity test, cointegration test and granger causality test.The research findings indicated that the national income (GDP) had a positive and significant influence on the Sharia and non-Sharia-compliant savings. The last test conducted was was the causality test and the result was that there was a two-way causal relationship between the national income and the Sharia-compliant savings, and there was a two-way causal relationship between the national income and the non-Sharia-compliant savings. However, as for the causal relationship between the variabel (Y) there was a one-way causal relationship between non-Sharia-compliant savings and Sharia-compliant savings.Keywords: Sharia-compliant savings, non-Sharia-compliant savings, National Income.